The elements of resilience in the food system and means to enhance the stability of the food supply - Rimhanen, Karoliina; Aakkula, Jyrki; Aro, Kalle; Rikkonen, Pasi (Springer Science and Business Media LLC, 2023)
Food systems are increasingly exposed to disruptions and shocks, and they are projected to increase in the future. Most recently, the war in Ukraine and Covid-19 pandemic has increased concerns about the ability to secure the availability of food at stable prices. This article presents a food system resilience framework to promote a national foresight system to better prepare for shocks and disruptions. Our study identified four key elements of resilience: system thinking through science and communication; redundancy of activities and networks; diversity of production and partners; and buffering strategies. Three national means to enhance resilience in the Finnish food system included domestic protein crop production, renewable energy production, and job creation measures. Primary production was perceived as the cornerstone for food system resilience, and the shocks and disruptions that it confronts therefore call for a sufficient and diverse domestic production volume, supported by the available domestic renewable energy. A dialogue between different actors in the food system was highlighted to format a situational picture and enable a rapid response. Our study suggests that to a certain point, concentration and interdependence in the food system increase dialogue and cooperation. For critical resources, sufficient reserve stocks buffer disruptions over a short period in the event of unexpected production or market disruptions. Introducing and strengthening the identified resilience elements and means to the food system call for the preparation of a more holistic and coherent food system policy that acknowledges and emphasises resilience alongside efficiency.
Keywords: Social-ecological system; Shocks; Changes; Food security; Resilience; Food system; Policy coherency; Finland